One method to define the concepts of physical quantities of derivatives - Kulviecas, L. (Psichologija, 1965)
The paper examines one of the methods of defining physical quantities of derivatives (known as the 1st definition method), which is widely used in physics and technical literature. This definition method clearly proved to be wrong, leading for false conclusions. In physics, the attitudes of calculation of physical quantities, namely, in terms of adopted unit systems in physics and technology, defining physical quantities of derivative using the 1st method is contrary to the known laws of mathematical logic and rules: to the law of contraposition, implications of transitivity laws, the implications of the matrix of equity value properties. Defining  physical quantities of derivative using the 1st method means equiparation of two dimensional vector spaces composed above the real number of the body (isomorphic), which consist of physical elements with regard to non-identical i.e., physical sizes. Such impermissible equiparation of the isomorphic vector spaces leads to various contradictions. Derivative size reveals the physical meaning of one-dimensional vector space to which it belongs, can be isomorphically displayed in another, different (one-dimensional) the vector space whose elements are physical quantities determined in a special way. The latter vector space can be chosen by more than one method.
Keywords: physics instruction; physics concepts; physical quantities definition